Sociodemographic and spatial disaggregation of e-commerce channel use in the grocery market in Great Britain. (July 2020) - Hood, Nick; Urquhart, Ryan; Newing, Andy; Heppenstall, Alison
Abstract: The UK Grocery e-commerce industry is amongst the most developed in the world with an estimated value of £11.4Billion in 2018. Assisted by technological developments, the market has experienced dramatic growth over the past two decades. Grocery retailers have invested in online infrastructure and home delivery networks. As a result, consumers have a range of options which enable them to shop interchangeably between in-store and online channels. The proliferation of new grocery shopping channels such as home delivery or 'click and collect' (collect in store or collection from a non-store collection point), coupled with changing consumer behaviour, provides new challenges for retailers in understanding consumer dynamics in this market. This paper explores consumer behaviour and preferences for e-commerce in the grocery retail industry in Great Britain (GB) using a survey of 19, 033 respondents from the major market research company YouGov. Respondents were asked a range of questions around uptake and channel usage in the grocery e-commerce sector. The survey presents a novel opportunity to analyse self-reported consumer behaviour in GB, with survey responses attached to key sociodemographic and locational information. We find that sociodemographics are an important driver of groceries e-commerce usage and channel choice, with females, more affluent households and those in the 25–44 age group most likely to use home delivery, corroborating previous research. Contrasting previous research, we also find statistically significant evidence of relatively high values of home delivery use among over-55s. Whilst overall usage is lower, we find a particular affinity to collection facilities among males and skilled manual workers. Spatially, we find evidence of both the innovation-diffusion theory and the efficiency theory at both a national and local authority district level, using a brief case study of Yorkshire and the Humber. These insights can support grocery retailers as they further develop costly localised infrastructure to support e-commerce. It could also assist retailers in understanding the localised drivers of channel choice as they seek to shift demand from home delivery (with high costs faced by the retailer in relation to the 'last mile') to click and collect (in which the customer faces the costs associated with the last mile).